Osteopathic intervention for infants with breastfeeding difficulty: A retrospective case series. (March 2023) - Greenwood, Kirsty; Engel, Roger; Grace, Sandra
Abstract: Background: The importance of breastfeeding and its effect on reducing the burden of disease is recognised globally. The physical aspect of successful breastfeeding is multifactorial and requires maternal comfort and confidence and an infant's ability to latch and maintain intra-oral sucking functions. Infants need to have sufficient function of their musculoskeletal system to maintain positioning and attachment. Objectives: The primary aim was to investigate the effect of osteopathic intervention on mothers and infants with breastfeeding difficulty. The secondary aim was to record the musculoskeletal dysfunctions found in those infants. Design: A retrospective case series of de-identified patient files. Setting: Osteopathic private practice. Methods: A Breastfeeding Self-Efficacy Scale and Visual Analogue Scale for maternal pain while feeding, ability to latch, ability to maintain latch and noise while feeding were completed before and after osteopathic intervention. Participants: Eighteen mother-infant-dyad files were retrospectively reviewed. Results: Following an average of five osteopathic treatments over 7.4 weeks, all 18 mother-infant-dyads noted improvement in breastfeeding confidence and/or improvements in the ability to latch and maintain latch, maternal pain at the breast and infant noise while feeding. The greatest improvements were seen in the seven mother-infant dyads identified at risk of ceasing breastfeeding at baseline (p=<0.001). Conclusion: This study provides evidence that osteopathic intervention may be capable of delivering benefits in breastfeeding confidence and function. Our results also indicate that osteopathic intervention may benefit mothers at risk of ceasing breastfeeding. Further research, including prospective clinical trials with a comparator group, is warranted. Highlights: IMPLICATIONS FOR PRACTICE. Osteopathic intervention appears to be safe. It has the potential to improve breastfeeding confidence and dysfunction in mother-infant dyads at risk of ceasing breastfeeding in infants under 10 weeks of age. Validated outcome measures are beneficial for determining the effect of osteopathic intervention in breastfeeding mothers at risk of ceasing breastfeeding. Expanding osteopathic clinical education to include breastfeeding observation as part of any management protocol for breastfeeding difficulties may improve patient care.